The Influence of Academic Coping And Friendship Quality on Elementary Students’ Learning Engagement - Fitria Yuningsih; Salwa Aulia Azzahra; Astri Istiqomah (CV. Akademi Merdeka, 2025)
This study aims to explore the relationship between academic coping strategies, friendship quality, and learning engagement of elementary school students within a single conceptual framework. A quantitative approach is used through a survey method, with the Partial Least Squares (PLS) analysis technique. The study subjects consisted of 240 students in grades 4 to 6 from three elementary schools. The results of data processing showed that the dimension of friendship quality had a significant influence on student engagement, while the contribution of academic coping strategies was identified as low and not statistically significant. The validity of ACOP constructions is also relatively weak, so it is necessary to develop a more representative instrument. These findings emphasize the important role of social relationships in shaping student engagement in schools, and suggest that educational programs focus more on strengthening supportive social interactions in the learning environment.